2016
DOI: 10.1097/inf.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Risk Factors for Nosocomial Infection in the Long Stay Critically Ill Child Without Known Baseline Immunocompromise

Abstract: Background Nosocomial infection remains an important health problem in long stay (> 3 days) pediatric intensive care unit (PICU) patients. Admission risk factors related to the development of nosocomial infection in long stay immune competent patients in particular are not known. Methods Post-hoc analysis of the previously published Critical Illness Stress induced Immune Suppression (CRISIS) prevention trial database, to identify baseline risk factors for nosocomial infection. Because there was no difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
1
12
0
3
Order By: Relevance
“…B cell deficiency could also impair the bacterial clearance by decreasing the production of inflammatory cytokines and chemokines, which are needed for neutrophil activation [33]. The data from critically ill children have shown that lymphocytopenia predisposed long-stay paediatric ICU (PICU) patients without known baseline immunocompromise to nosocomial infection [34]. In a recent study focused on patients with shock in ICU, lymphocytopenia on admission was also found to increase the nosocomial infection, which partially supported our findings [35].…”
Section: Discussionsupporting
confidence: 84%
“…B cell deficiency could also impair the bacterial clearance by decreasing the production of inflammatory cytokines and chemokines, which are needed for neutrophil activation [33]. The data from critically ill children have shown that lymphocytopenia predisposed long-stay paediatric ICU (PICU) patients without known baseline immunocompromise to nosocomial infection [34]. In a recent study focused on patients with shock in ICU, lymphocytopenia on admission was also found to increase the nosocomial infection, which partially supported our findings [35].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, secondary acquired infections represent a major economic burden by significantly extending length of hospital stay [ 41 , 42 ], and concordantly herein the length of hospitalization in those with secondary infection doubled (and this difference was significant). Taken together, these data reinforce the idea that most immunosuppressed septic children might benefit from immunostimulation as an adjunctive therapy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nosocomial infections are an important health problem even in children who stay more than 3 days in the PICU. Carcillo et al 18 found that increasing age, cardiac arrest, or lymphopenia predisposed long-stay PICU patients to nosocomial infections. Furthermore, it has been reported that resistant bacterial infections can result in significantly increased LOS in the ICU, which increases the economic burden of treating those patients and increases the load on health care providers.…”
Section: Discussionmentioning
confidence: 99%